SANKSI PIDANA TERHADAP PELAKU ILLEGAL LOGGING - Pramana Putra, Wayan Satria; Swardhana, Gde Made; Darmadi, A.A. Ngr. Yusa (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 01, Januari 2013)
This paper entitled “Criminal Sanctions Against Illegal Logging Actors”. Thispaper uses normative analysis method. Refers to the rate ofdeforestation rateinIndonesiais gettingworse,Illegallogging is acriminaloffensewith global implications.Many ways toanticipatethe widespreadcrime.Thatone way tomake therulesthat governitand providemaximumpunishmentto theperpetrators. Penal systemisthe mostappropriate waytopreventand solvecrimeof illegallogging.Key words: Illegal Logging, rules,maximum punishment, Penal system
Keywords: Illegal Logging, Pengaturan, Hukuman maksimal, Sistem pidana